2007
DOI: 10.1103/physrevlett.99.187002
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Evidence for a Fulde-Ferrell-Larkin-Ovchinnikov Superconducting State in the Layered Organic Superconductorκ(BEDTTTF)2Cu(

Abstract: The specific heat of the layered organic superconductor -BEDT-TTF 2 CuNCS 2 , where BEDT-TTF is bisethylenedithio-tetrathiafulvalene, has been studied in magnetic fields up to 28 T applied perpendicular and parallel to the superconducting layers. In parallel fields above 21 T, the superconducting transition becomes first order, which signals that the Pauli-limiting field is reached. Instead of saturating at this field value, the upper-critical-field increases sharply and a second first-order transition line ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
243
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(269 citation statements)
references
References 32 publications
(33 reference statements)
23
243
3
Order By: Relevance
“…These experimental results are interpreted as evidence for the existence of the FFLO phase. Similar behavior is observed in organic superconductors [14].…”
Section: Summary and Final Remarkssupporting
confidence: 65%
See 2 more Smart Citations
“…These experimental results are interpreted as evidence for the existence of the FFLO phase. Similar behavior is observed in organic superconductors [14].…”
Section: Summary and Final Remarkssupporting
confidence: 65%
“…in multiband superconductors like IBSC [33][34][35][36] or MgB 2 [37,38]. Specific heat measurements have been also successfully used to investigate the FFLO phase in heavy-fermion systems [7,8,11] and organic superconductors [14], where the peaks, deep in the superconducting state in the LTHM regime, have been interpreted as phase transitions from BCS to FFLO state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34) While a Larkin-Ovchinnikov (LO) state, characterized by the magnitude modulation of the superconducting order parameter, is expected in centrosymmetric superconductors, 35) a Fulde-Ferrell (FF) state, a "helical phase" with an essentially constant order parameter magnitude, 3,[9][10][11][12][13][14][15] could appear in non-centrosymmetric superconductors exposed to a magnetic field. Although experimental indications of the realization of an LO phase have been found for the heavy-fermion superconductor CeCoIn 5 , 36,37) organic superconductors, [38][39][40] ultracold fermion gases with a population imbalance, 41) and nuclear matter, 42) there has been no experimental evidence of the helical phase in non-centrosymmetric superconductors so far. In this paper, we show that a complex-stripe phase, which can be viewed as intermediate between FF and LO states, may exist in locally non-centrosymmetric multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Following the theoretical prediction of Fulde and Ferrell 1) and Larkin and Ovchinnikov, 2) there has been no convincing experimental evidence of this FFLO state. However, recently, it has been suggested that it occurs in strongly Pauli-limited clean type-II superconductors, such as the heavy-fermion superconductor CeCoIn 5 4) and the quasi-low-dimensional organic superconductors κ-(BEDT-TTF) 2 Cu(NCS) 2 , [10][11][12][13] λ-(BETS) 2 FeCl 4 , [16][17][18] λ-(BETS) 2 GaCl 4 , 19) and (TMTSF) 2 ClO 4 . [20][21][22][23][24][25][26][27] Quasi-low-dimensionality is a common feature of the above-mentioned compounds.…”
Section: Introductionmentioning
confidence: 99%